Activities of four macrolides, including clarithromycin, against Mycobacterium fortuitum, Mycobacterium chelonae, and M. chelonae-like organisms. - Brown, B A (1992)
Susceptibilities to erythromycin by broth microdilution were compared with those to the newer macrolide clarithromycin for 223 isolates of rapidly growing mycobacteria belonging to seven taxonomic groups. Seventy-nine random isolates were also tested against azithromycin and roxithromycin. The MIC of clarithromycin for 90% of strains tested (MIC90) was 0.25 microgram/ml for isolates of Mycobacterium chelonae subsp. chelonae and 0.5 microgram/ml for M. chelonae subsp. abscessus, with 100% of strains inhibited by less than or equal to 1 microgram/ml. Clarithromycin was 10 to 50 times more active than erythromycin and four- to eightfold more active than the other newer macrolides against M. chelonae. MICs of clarithromycin frequently increased with prolonged incubation with isolates of M. chelonae subsp. abscessus but not M. chelonae subsp. chelonae. MICs of clarithromycin were much higher for M. fortuitum bv. fortuitum (MIC50, 2.0 microgram/ml; MIC90, greater than 8.0 microgram/ml). The three newer macrolides had comparable activity against M. fortuitum bv. peregrinum (MIC90s of 0.5 to 2.0 microgram/ml compared with erythromycin MIC90s of greater than 8.0 microgram/ml). Overall, clarithromycin was the most active agent, inhibiting all isolates of M. chelonae subsp. chelonae, M. chelonae subsp. abscessus, M. fortuitum bv. peregrinum, and the M. chelonae-like organisms and 35% of M. fortuitum bv. fortuitum at less than or equal to 1 microgram/ml. Clinical trials of the newer macrolides, especially clarithromycin, against these environmental mycobacterial species appear to be warranted.